Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1007/s00436-011-2585-z
|View full text |Cite
|
Sign up to set email alerts
|

ImmunoCard STAT! cartridge antigen detection assay compared to microplate enzyme immunoassay and modified Kinyoun's acid-fast staining technique for detection of Cryptosporidium in fecal specimens

Abstract: Cryptosporidium species infect humans and a wide range of animals worldwide; outbreaks of cryptosporidiosis have been reported in several countries. Routine diagnostic methods may be insufficient to demonstrate the presence of these organisms. The study assessed the diagnostic accuracy of the antigen detection immuno-cartridge test, ImmunoCard STAT! (Meridian Bioscience Inc., Cincinnati, OH, USA), compared to the combined gold standard: modified Kinyoun's acid-fast technique confirmed with the microplate enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…The modified ZiehlNeelsen technique (413) is used widely; however, one recent study found that it was less sensitive than PCR (75.7%; 95% CI ϭ 68.3 to 81.8%) but was highly specific (100%; 95% CI ϭ 96.5 to 100%) (56). Kinyoun's acid-fast staining technique (102), modified Sheather's flotation technique (76,294,296), and the iron-hematoxylin staining technique (119) have also been described.…”
Section: Cryptosporidium Speciesmentioning
confidence: 99%
“…The modified ZiehlNeelsen technique (413) is used widely; however, one recent study found that it was less sensitive than PCR (75.7%; 95% CI ϭ 68.3 to 81.8%) but was highly specific (100%; 95% CI ϭ 96.5 to 100%) (56). Kinyoun's acid-fast staining technique (102), modified Sheather's flotation technique (76,294,296), and the iron-hematoxylin staining technique (119) have also been described.…”
Section: Cryptosporidium Speciesmentioning
confidence: 99%
“…Such conflicting evaluations reduce the advantage of rapid detection of Cryptosporidium by ICT immunoassay, which may be explained by the persistence of antigens for several days after treatment, or an abortive infection, or by cross-reaction with other antigens [42] . It was reported that several mAbs against oocysts antigens of C. parvum cross react with other parasitic life cycle stages, other Cryptosporidium species or other coccidian parasites [43,44] . Because reaction of the immuno-card test may persist after the patient stops shedding intact organisms, our results may not be false-positive but may rather represent recently cured cases [45] .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have previously identified these tests as having sensitivity and specificity similar to the performance of DFA, the gold standard test for Cryptosporidium [1820]. However, previous problems with false-positive results associated with these tests have been noted [19, 24, 25].…”
Section: Discussionmentioning
confidence: 99%
“…When exposed to fecal specimens with Cryptosporidium antigen, a cartridge containing proprietary capture antibody for the antigen will cause a colored line (Remel Xpect, red for Cryptosporidium ; Meridian Immunocard STAT!, gray-black) to appear in addition to a line in the control window. In previous studies, these assays were reported to perform well compared to other diagnostics assays [1820]. …”
Section: Introductionmentioning
confidence: 99%